2020
DOI: 10.3389/fmicb.2020.00608
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role for Acyl-CoA Binding Domain Containing 3 at Membrane Contact Sites During Viral Infection

Abstract: Acyl-coenzyme A binding domain containing 3 (ACBD3) is a multifunctional protein residing in the Golgi apparatus and is involved in several signaling pathways. The current knowledge on ACBD3 has been extended to virology. ACBD3 has recently emerged as a key factor subverted by viruses, including kobuvirus, enterovirus, and hepatitis C virus. The ACBD3-PI4KB complex is critical for the role of ACBD3 in viral replication. In most cases, ACBD3 plays a positive role in viral infection. ACBD3 associates with viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…1 D ). Several research groups demonstrated that PI4KB and ACBD3 are pivotal host factors for the propagation of picornaviruses ( Sasaki et al, 2012 ; Greninger et al, 2012 ; Lyoo et al, 2019 ; also reviewed in Lu et al, 2020 ). In addition, Burke and his colleagues showed that C10orf76 participates in the organization of the PI4KB-dependent enterovirus replication complex ( McPhail et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 D ). Several research groups demonstrated that PI4KB and ACBD3 are pivotal host factors for the propagation of picornaviruses ( Sasaki et al, 2012 ; Greninger et al, 2012 ; Lyoo et al, 2019 ; also reviewed in Lu et al, 2020 ). In addition, Burke and his colleagues showed that C10orf76 participates in the organization of the PI4KB-dependent enterovirus replication complex ( McPhail et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…TBC1D22A and TBC1D22B [75]. An excellent review of the roles of ACBD3 in viral replication was just published [79]. High-resolution structures of ACBD3 with truncated versions of 3A from several Enteroviruses and Picornaviruses were recently released [80][81][82].…”
Section: Acbd3 -Gcp60mentioning
confidence: 99%
“…In this case, the interactions involve the same sites in the C‐terminal GOLD domain of ACBD3 used to interact with members of the putative Rab33 GTPase‐activating proteins TBC1D22A and TBC1D22B [75]. An excellent review of the roles of ACBD3 in viral replication was just published [79]. High‐resolution structures of ACBD3 with truncated versions of 3A from several Enteroviruses and Picornaviruses were recently released [80–82].…”
Section: Acbd3 – Gcp60mentioning
confidence: 99%
“…ACBD3 is a Golgi resident protein that recruits PI4KIIIβ to the Golgi and trans -Golgi network (TGN) and stimulates its enzymatic activity to produce PI4P ( Sohda et al, 2001 ; Baumlova et al, 2014 ; Boura and Nencka, 2015 ). Using infection models of Enteroviruses A71 (EV-A71), D68 (EV-D68), Rhinovirus , and Poliovirus various groups have demonstrated that 3A protein binds with GOLD domain of ACBD3 and knockdown of either ACBD3 or PI4KIIIβ perturbs replication of these viruses signifying the role of PI4P and OSBP in enterovirus replication ( Greninger et al, 2012 ; Rönnberg et al, 2012 ; Nchoutmboube et al, 2013 ; Téoulé et al, 2013 ; Lei et al, 2017 ; Lu et al, 2020 ). A recent study contradicted the above finding, and shown that trans -rescue of EV-A71 pseudo virus replication with PI4KIIIβ deletion mutants suggested that the ACBD3-binding site of PI4KIIIβ is not essential for EV-A71 or poliovirus replication ( Arita, 2019 ).…”
Section: Lipid Transfer Proteins In the Viral Life Cyclementioning
confidence: 99%